The Rule of Law and Security Sector Reform : Conceptualising a Complex Relationship - Bleiker, Christoph; Krupanski, Marc (London Ubiquity Press, 2012)
There is a clear need to better understand the relationship between two concepts at the heart of peacebuilding: the Rule of Law (RoL), and Security Sector Reform (SSR). If it is acknowledged in principle that they are interdependent, in practice enduring conceptual ambiguities and contradictions undermine latent synergies. As a consequence, international donor agencies are under increasing pressure to demonstrate the benefits of their RoL and SSR assistance. This SSR Paper moves the RoL-SSR debate forward through examining these activities jointly within a peacebuilding context. It proposes a heuristic framework that helps to rationalize this relationship on a conceptual level, demonstrating that RoL and SSR are interdependent and mutually reinforcing. The resulting framework provides a basis for the development of coherent policies that can support the development of coordinated, complementary programmes on the ground.
English
Keywords: Politics & government; Warfare & defence; security sector reform; good governance; rule of law; human rights; peacebuilding; United Nations